2011
DOI: 10.1097/01.yic.0000405901.80483.0b
|View full text |Cite
|
Sign up to set email alerts
|

A functional alternative splicing mutation in human tryptophan hydroxylase-2

Abstract: The brain serotonergic system has an essential role in the physiological functions of the central nervous system and dysregulation of serotonin (5-HT) homeostasis has been implicated in many neuropsychiatric disorders. The tryptophan hydroxylase-2 (TPH2) gene is the rate-limiting enzyme in brain 5-HT synthesis, and thus is an ideal candidate gene for understanding the role of dysregulation of brain serotonergic homeostasis. Here, we characterized a common, but functional single-nucleotide polymorphism (SNP rs1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…29 These observations as well as the recent characterization of a dominant negative form of TPH2 significantly affecting 5-HT synthesis that is present in roughly 20% of the general population may justify consideration of such a genotyping strategy. 32,33 The present study shows that both synthesis and SERTmediated reuptake are essential for maintaining proper intraneuronal 5-HT levels and persistent blockade of SERT by SSRIs exacerbates 5-HT deficiency in subjects with impaired TPH2 function. Finally, supplemental treatments with 5-HTP could prevent depletions caused by SSRIs in subjects with 5-HT synthesis deficiency.…”
Section: ■ Results and Discussionmentioning
confidence: 60%
“…29 These observations as well as the recent characterization of a dominant negative form of TPH2 significantly affecting 5-HT synthesis that is present in roughly 20% of the general population may justify consideration of such a genotyping strategy. 32,33 The present study shows that both synthesis and SERTmediated reuptake are essential for maintaining proper intraneuronal 5-HT levels and persistent blockade of SERT by SSRIs exacerbates 5-HT deficiency in subjects with impaired TPH2 function. Finally, supplemental treatments with 5-HTP could prevent depletions caused by SSRIs in subjects with 5-HT synthesis deficiency.…”
Section: ■ Results and Discussionmentioning
confidence: 60%
“…It is noteworthy that a C-terminal truncated TPH2 splice variant (TPH2-TR), which lacks TPH2 enzyme activity, dominant-negatively affects the full-length TPH2 function and results in reduced 5-HT synthesis [88]. Accordingly, another strategy for the modulation of TPH2 activity is to modify the alternative splicing of TPH 2 pre-mRNA.…”
Section: Tph2 As An Emerging Therapeutic Target For Stress Disordersmentioning
confidence: 99%
“…More recently, Zhang et al [2010a] reported that a common SNP (G>A, rs1386493) in intron 5 of h TPH 2 decreases efficiency of normal RNA splicing and results in a truncated TPH2 protein (TPH2‐TR) by alternative splicing. This TPH2‐TR lacks TPH2 enzyme activity but dominant‐negatively affects full‐length TPH2 function, causing reduced 5‐HT production [Zhang et al, 2010a].…”
Section: Introductionmentioning
confidence: 99%
“…This TPH2 mRNA variant is 2,992‐bp long and comprises six or seven exons, with the first five exons identical with the normal TPH2 mRNA while the last two exons are derived from intron 5. Hence, this shortened mRNA variant results not only from transcriptional regulation through alternative promoter usage, but also from post‐transcriptional regulation by alternative splicing, which is affected by an exon–intron boundary SNP (rs1386493) as mentioned above [Zhang et al, 2010a]. As for the strong antisense promoter in TPH 2 5′‐UTR, it may transcribe an antisense non‐coding RNA that partially overlaps the conventional TPH 2 mRNA, such that dsRNA might be formed to regulate TPH 2 gene expression.…”
Section: Introductionmentioning
confidence: 99%